Christian Teacher Ethics in Society 5.0: Integrating Faith Values in Digital Education - Hia, Meniati (Jurnal Didaskalia, 2025)
The transformation toward Society 5.0 presents complex challenges for Christian education in maintaining faith values while integrating technological advancement. This study analyzes the ethics of Christian teacher professionalism in the Society 5.0 era through practical theology and educational philosophy perspectives using qualitative research methods with theological hermeneutic approaches and systematic literature analysis. The research explores how Christian values can be applied in increasingly digital and connected educational contexts through examination of biblical principles, theological frameworks, and contemporary educational practices. Findings indicate that Christian teacher professionalism in the Society 5.0 era requires ethical reconstruction including: (1) technology theology centered on imago Dei as anthropological foundation, (2) transformative pedagogy based on agape love as pedagogical motivation, (3) learning communities reflecting koinonia as community model, and (4) educational service as diakonia expressing service orientation. This research contributes to developing a comprehensive ethical framework for Christian teacher professionalism that effectively responds to Society 5.0 technological challenges while preserving faith integrity and Christian educational mission, providing practical implementation strategies for educational institutions, teachers, and policymakers in the digital transformation era.